Optimal target blood pressure level for elderly with hypertension - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Target pressure <140/90 mm Hg allows better prevention of cardiovascular events, but this requires a more detailed examination.